Understanding Sex Differences in Form and Function of Bird Song: The Importance of Studying Song Learning Processes - Riebel, Katharina (Frontiers in Ecology and Evolution, 2016)
Birdsong is a culturally transmitted mating signal. Due to historical and geographical biases, song (learning) has been predominantly studied in the temperate zones, where female song is rare. Consequently, mechanisms and function of song learning have been almost exclusively studied in male birds and under the premise that inter- and intrasexual selection favoured larger repertoires and complex songs in males. However, female song is not rare outside the temperate zones and song in both sexes probably is the ancestral state in songbirds. Some song dimorphisms seen today might therefore be manifestations of secondary losses of female song. What selection pressures have favoured such losses and other sexual dimorphisms in song? Combined mapping of phylogenetic and ecological correlates of sex differences in song structure and function might provide important clues to the evolution of male and female song. This requires parameterization of the degree of sexual dimorphism. Simple comparison of male-female song might not provide enough resolution, because the same magnitude of difference (e.g. repertoire overlap) could result from different processes: the sexes could differ in how well they learn (‘copying fidelity’) or from whom they learn (‘model selection’). Different learning mechanisms might provide important pointers towards different selection pressures. Investigating sex-specific learning could therefore help to identify the social and ecological selection pressures contributing to sex differences in adult song. The study of female song learning in particular could be crucial to our understanding of i) song function in males and females and ii) the evolution of sex-specific song.